Work and knowledge of mother readiness in exclusive breastfeeding - Mulyani, Sri (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
Knowledge of exclusive breastfeeding has been proven, through previous studies, as one of the factors that affect the readiness of pregnant mothers in exclusive breastfeeding. It is also widely reported about the job or profession mothers (especially those done outside the home) as factors inhibiting the implementation of exclusive breastfeeding. This study aims to examine the role of the moderator job as the relationship between knowledge of exclusive breastfeeding with maternal readiness in exclusive breastfeeding. Cross-sectional study performed on pregnant women with first child, a sample of 139 respondents was taken to the criteria does not work (housewives) or working outdoors. Enclosed questionnaire was used to measure the knowledge and readiness of mothers in exclusive breastfeeding. The data analysis technique used is the linear regression model. The results showed that the significant effect of knowledge on the readiness of pregnant women at work (R = 0.412; p = 0.002) but not significant in pregnant women who do not work (R = 0.187; p = 0.086). It can be concluded that the work has a role as moderator effect of exclusive breastfeeding knowledge about the readiness of pregnant mothers in exclusive breastfeeding.